2015
DOI: 10.1590/0103-8478cr20140565
|View full text |Cite
|
Sign up to set email alerts
|

Response of soil microbiota to nine-year application of swine manure and urea

Abstract: Manure fertilization is a common practice, but little is known about its impacts on soil microbial activity and organic matter. Aiming to evaluate soil microbial response to nine years of successive applications of swine manure, organic carbon (TOC), total nitrogen (TN), pH, microbial biomass carbon (MBC), basal respiration (BR), metabolic quotient (qCO 2 ), and enzyme (ß-glucosidase, phosphatase, arylsulphatase, and FDA)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 16 publications
0
8
0
6
Order By: Relevance
“…), Morales et al (2016) found no effect even after the application of 209 kg N as PLW ha -1 yr -1 for fourteen years. Thus, in soils with low initial content of organic matter, organic carbon added via pig manure provides a source of energy and organic and inorganic nutrients to the soil microorganisms and boosts the microbial biomass.…”
Section: Microbiological Characteristicsmentioning
confidence: 83%
“…), Morales et al (2016) found no effect even after the application of 209 kg N as PLW ha -1 yr -1 for fourteen years. Thus, in soils with low initial content of organic matter, organic carbon added via pig manure provides a source of energy and organic and inorganic nutrients to the soil microorganisms and boosts the microbial biomass.…”
Section: Microbiological Characteristicsmentioning
confidence: 83%
“…Dessa forma, informações sobre o estado da agregação da camada superficial do solo constituem-se em indicadores de qualidade relativamente simples e sensíveis às mudanças decorrentes da adição de dejetos de suínos ao solo como via de fornecimento de nutrientes para as plantas. O aumento da atividade biológica nas áreas com adição de dejetos suínos (Morales et al 2016) resultou em alterações nas diferentes vias de formação de agregados, tais como a maior porcentagem de agregados biogênicos em relação aos fisiogênicos. A manutenção da palhada vegetal sobre o solo, a ausência de revolvimento do mesmo e a adição dos dejetos de suínos acarretam em melhores condições físicas e químicas, com posterior aumento da fauna do solo, principalmente minhocas (Anghinoni et al, 2011).…”
Section: Resultsunclassified
“…Os maiores valores de macroagregados observados nos tratamentos com CSS também podem estar relacionados com a maior atividade microbiana encontrada nesses tratamentos quando comparado aos demais (Morales et al, 2016), resultando na formação de macroagregados por ação de forças eletrostáticas, atividade microbiana e crescimento de raízes (Six et al, 2000). A maior quantidade de macroagregados nos tratamentos com CSS na profundidade de 5-10cm acarreta em melhores condições físicas para o desenvolvimento radicular das culturas, sendo verificado nesta mesma área de estudo, segundo Comin et al (2013), menores valores de densidade do solo e resistência a penetração, assim como maiores valores de macroporosidade nos tratamentos com CSS.…”
Section: Diâmetro Médio Ponderado Dos Agregadosunclassified
“…Sedangkan pada lahan yang jumlah mikroorganisme paling tinggi ternyata kandungan %C-organiknya sangat tinggi juga mencapai 8.15% (BPT 2009). Menurut Morales et al (2016), aplikasi kotoran hewan yang sering diberikan dalam pemupukan akan meningkatkan jumlah total mikroorganisme tanah dan aktivitasnya di dalamtanah dan juga meningkatkan %C-organik tanah. Sedangkan aplikasi urea yang terlalu sering dalam pemupukan akan berdampak negatif terhadap indikator aktivitas mikroorganisme tanah dan menurunkan juga %C-organik yaitu bahan organik tanah (Morales et al, 2016).…”
Section: Uji Korelasi Dataunclassified
“…Menurut Morales et al (2016), aplikasi kotoran hewan yang sering diberikan dalam pemupukan akan meningkatkan jumlah total mikroorganisme tanah dan aktivitasnya di dalamtanah dan juga meningkatkan %C-organik tanah. Sedangkan aplikasi urea yang terlalu sering dalam pemupukan akan berdampak negatif terhadap indikator aktivitas mikroorganisme tanah dan menurunkan juga %C-organik yaitu bahan organik tanah (Morales et al, 2016). Xiao et al (2017) berpendapat bahwa sangat sedikit yang diketahui tentang jumlah total mikroorganisme tanah yang dikaitkan dengan erosi tanah, tapi semua itu disebabkan oleh keberadaan yang terus menerus dari bahan organik tanah dilahan tersebut.…”
Section: Uji Korelasi Dataunclassified